2003
DOI: 10.1046/j.1464-5491.2003.01010.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the rapid‐acting insulin analogue insulin aspart on quality of life and treatment satisfaction in patients with Type 1 diabetes

Abstract: Under these study conditions, IAsp improved treatment satisfaction and quality of life regarding diet restrictions when compared with human insulin. The 'numbers needed to treat' for important quality of life benefits indicate that the effect of IAsp in this regard is not trivial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
53
1
5

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 33 publications
1
53
1
5
Order By: Relevance
“…In the current study, however, the between-group difference in the DTSQs treatment satisfaction score was much greater, at 8.6. The between-group differences in each of the items of the DTSQs in the current study were also much greater than those reported in previous studies comparing insulin glargine with NPH insulin or rapidacting insulin analogs with unmodified human insulin (4,13,22). This result suggests that the combination of insulin glargine and a rapid-acting insulin analog might have a synergistic benefit on treatment satisfaction.…”
Section: Addqolcontrasting
confidence: 63%
See 2 more Smart Citations
“…In the current study, however, the between-group difference in the DTSQs treatment satisfaction score was much greater, at 8.6. The between-group differences in each of the items of the DTSQs in the current study were also much greater than those reported in previous studies comparing insulin glargine with NPH insulin or rapidacting insulin analogs with unmodified human insulin (4,13,22). This result suggests that the combination of insulin glargine and a rapid-acting insulin analog might have a synergistic benefit on treatment satisfaction.…”
Section: Addqolcontrasting
confidence: 63%
“…Rapid-acting insulin analogs have been shown to improve treatment satisfaction compared with unmodified human insulin in individuals with type 1 diabetes, with reported between-group differences in the DTSQs treatment satisfaction score of 1.6 -2.3 (11)(12)(13)(14). Similar studies have reported improvements in the DTSQs treatment satisfaction score with insulin glargine compared with NPH insulin of 0.9 -1.8 (4,21).…”
Section: Addqolmentioning
confidence: 99%
See 1 more Smart Citation
“…O uso da insulinoterapia em algumas pesquisas está associado a valores baixos de QV (20,21); em outras pesquisas, o uso da insulina pode melhorar a QV (22)(23)(24), ou até mesmo não influenciá-la (25). A avaliação de QV em pacientes diabéticos é bem mais complexa e inter-relacionada e a insulinoterapia pode levar ao melhor controle glicêmico, mas também pode aumentar o risco de hipoglicemia em pacientes com DM.…”
Section: Diabetes Melito E Qualidade De Vidaunclassified
“…The availability of insulin analogues enhances flexibility and convenience for insulin-treated patients, and this increased flexibility in insulin timing is associated with an improvement in quality-of-life measures (25). The increasing variety of insulin preparations allows more opportunities to achieve control.…”
mentioning
confidence: 99%